A multiple model filtering approach to transmission line fault diagnosis. (July 2016) - Qin, Qiu; Wu, N. Eva
Abstract: This paper provides justification and implementation for a multiple model filtering approach to diagnosis of transmission line three-phase short to ground faults in the presence of protection misoperations. This approach utilizes the electric network dynamics and wide area measurements to provide diagnosis outcomes. A second focus of this paper is on the reduction of computational complexity of the diagnosis algorithm. This issue is addressed by a two-step heuristic. The first step designs subsystem models through measurement selection. The second step reduces the dynamic model order. The performance of the diagnosis algorithms are evaluated on a simulated WSCC 9-bus system. Abstract : Highlights: Applied multiple model approach to diagnosis of transmission line faults. Fault diagnosis was based on electric network dynamics and wide area measurements. Proposed a two-step procedure to reduce computational complexity.